Post-Exercise Sweat Loss Estimation Accuracy of Athletes and Physically Active Adults: A Review - Eric O'Neal; Tara Boy; Brett Davis; Kelly Pritchett; Robert Pritchett; Svetlana Nepocatych; Katherine Black (MDPI AG, 2020)
The main purposes of this review were to provide a qualitative description of nine investigations in which sweat losses were estimated by participants following exercise and to perform a quantitative analysis of the collective data. Unique estimations (n = 297) were made by 127 men and 116 women after a variety of exercise modalities in moderate to hot environmental conditions. Actual sweat loss exceeded estimated sweat loss (p < 0.001) for women (1.072 ± 0.473 vs. 0.481 ± 0.372 L), men (1.778 ± 0.907 vs. 0.908 ± 0.666 L) and when all data were combined (1.428 ± 0.806 vs. 0.697 ± 0.581 L), respectively. However, estimation accuracy did not differ between women (55.2 ± 51.5%) and men (62.4 ± 54.5%). Underestimation of 50% or more of sweat losses were exhibited in 168 (54%) of estimation scenarios with heavier sweaters displaying a higher prevalence and trend of greater underestimations in general. Most modern guidelines for fluid intake during and between training bouts are based on approximate sweat loss estimation knowledge. These guidelines will likely have minimal efficacy if greater awareness of how to determine sweat losses and accurate recognition of sweat losses is not increased by coaches and athletes.